Effect of Feeding Mango and Senna occidentalis Leaf Meals as Replacement to Prophylactic Antibiotic Use on Performance of Broiler Chickens - Usman, Hussaina B.; Sabo, Mustapha N.; Sadisu, A. B.; Mbakwe , Chinedum C.; Jibia, Zainab Saminu; Sulaiman, Aliyu (Sahel Journal of Life Sciences FUDMA, 2024)
A total of 180-day-old broiler chicks were used to evaluate the effect of feeding mango and Senna leaf meal as a replacement to prophylactic antibiotics use on the performance of broiler chickens. The birds were fed mango (MLM) and senna leaf meal (SLM) at 0g, 5gMLM, 7.5gMLM, 5gSLM and 7.5gSLM as treatments in a completely randomized design. Data on phytochemicals, growth performance, carcass characteristics, and haematological and serum biochemical parameters were collected. Data collected were subjected to variance analysis. The results show that flavonoids, alkaloids, saponins, tannin and phenol were present in Mango and Senna leaf meals. Total feed costs in diets containing the different levels of MLM and SLM were lower (P<0.05) compared to the control. The feed cost per kg gain was also higher (P<0.05) in the control group compared to 5gMLM. Mortality was higher in the control compared to those fed the different leaf meals. The breast weight of the 5gMLM was higher (P<0.05) than that of 7.5gMLM and 5gSLM. The PCV of the group fed with 5gSLM was lower (p<0.05) compared to the control group and those fed with 5gMLM, 7.5gMLM, and 7.5gSLM. The WBC was higher (p<0.05) in the control group and 5gSLM compared to those fed with 5gMLM and 7.5gSLM. From the results, it can be concluded that 5gM resulted in better growth performance without adverse effects on haematological and serum biochemical parameters. Hence, it is recommended that 5gMLM can be used in the diets of broiler chickens in place of prophylactic antibiotics.